Management and control of non-direct materials in an electronic company - Musa, Hamidon; Mat Saman, Muhamad Zameri; Hau, Lian Chuan (Faculty of Mechanical Engineering, 2002)
The paper is based on a study aimed at establishing a management model used to control non-direct materials (NDM) in an electronic company. A set of procedures has been developed to address several problems associated with previous practices in the company. Examples of the problems are unavailability of procedures in NDM repair and scrap process, inefficiencies in tracking the actual quantity and investment cost of NDM and etc. A computer database system has been developed to assist the implementation of the management model.